Rhetoric and Stylistics - Abu Shufa, Bashir Ibrahim ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2015)
In recent years, the academic discourse has witnessed an increasing focus on the relationship between stylistics as a modern critical methodology and classical Arabic rhetoric as a core component of the Arab-Islamic intellectual heritage. This study explores the conceptual and methodological boundaries of both fields and aims to determine the nature of the relationship between them—whether it be convergence, divergence, or complementarity. Adopting a descriptive and analytical approach, the research draws upon classical sources on Arabic rhetoric and contemporary references on stylistics and stylistic analysis. The study is structured into three main sections: the first outlines foundational concepts; the second examines the points of convergence and divergence between stylistics and rhetoric; and the third analyzes the nature of their relationship in both Arabic and Western contexts. The research concludes with key findings and recommendations. Ultimately, this work seeks to bridge the gap between two fields that have traditionally been studied in isolation, despite their potential intersections.